Phylogenetic position of Vicia montbretii and Lens species in relation to Vicia subgenus Cracca (Fabaceae): morphological and isozyme evidence. Issue 3 (20th February 2019) - Leht, Malle; Jaaska, Vello
Abstract : The Near East endemic vetch Vicia montbretii is a taxonomically controversial species because it has been also treated either as Ervum kotschyanum or Lens montbretii . The phylogenetic affinity and taxonomic treatment of Lens species in relation to Vicia has become debatable. We studied variation of morphological and isozyme characters in V. montbretii, Lens odemensis, L. orientalis and L. nigricans in comparison to 19 species of Vicia subgenus Cracca and three Lathyrus outgroup species in order to get evidence about their systematic and phylogenetic position. The cladistic analysis of morphology revealed that V. montbretii is tightly connected with Lens species and the Ervum group. The cladistic analysis of isozymes placed V. montbretii and the three Lens species in subgenus Cracca as divergent subclades. V. montbretii differs from the Lens species in ten isozymes out of 16 analysed. Vicia montbretii appears sister to Vicia sections Cracca, Panduratae and Pedunculatae, whereas the Lens subclade is linked to the subclade of Vicia sections Ervoides, Ervilia and Lenticula . The consistencies and differences between the morphological and molecular characters (isozymes plus DNA sequences) are discussed.